2017
DOI: 10.1038/s41598-017-08759-4
|View full text |Cite
|
Sign up to set email alerts
|

Optical spin noise spectra of Rb atomic gas with homogeneous and inhomogeneous broadening

Abstract: We study the optical spin noise spectra of Rb atomic gas with different broadening mechanisms. The first is homogeneous broadening using 250 Torr nitrogen buffer gas, while the other mechanism is inhomogeneous broadening via the Doppler effect without buffer gas. Spin noise signals are measured by the typical spin noise spectroscopy geometry (single-pass geometry) and the saturated absorption spectroscopy geometry (double-pass geometry). In the homogeneously broadened system, the line shape of the optical spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
9
1
Order By: Relevance
“…7(b)] can be used to measure homogeneous width of the transition [27]. This situation is realized in quantum dot structures [8,18] and in the collisionless atomic gases [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7(b)] can be used to measure homogeneous width of the transition [27]. This situation is realized in quantum dot structures [8,18] and in the collisionless atomic gases [26].…”
Section: Discussionmentioning
confidence: 99%
“…These works have shown that (i) the spin noise (SN) signal is the greatest for the probe beam tuned at maximum of the absorption band [8] and (ii) in the two-color experiment, where two linearly polarized probe beams with different wavelengths are used, the correlations between the fluctuating FR of the beams are absent unless the detuning between the beams becomes comparable with the homogeneous linewidth of the optical transition [18]. In recent work [26] the two limiting cases of homogeneous and inhomogeneous broadening have been arXiv:1709.07959v2 [physics.atom-ph] 26 Oct 2017 realized in Rb gas vapors.…”
Section: Introductionmentioning
confidence: 99%
“…and low-dimensional media (e. g. [16,17]) can be addressed by SNS, but also the nuclear dynamics [18][19][20], light-matter interaction effects [21,22], spatial properties distribution [23,24], and even noise of valley redistribution of electrons [25]. Still the atomic systems attract the significant attention of researchers [26][27][28][29][30][31][32][33] as model objects which allow to reveal the fundamental pecularities of spin noise formation mechanics. In typical SNS experiments with polarimetric detection of the signal, one measures, in fact, the magnetization-noise power spectrum of the studied sample associated, in accordance with the fluctuation-dissipation theorem, with the spectrum of its magnetic susceptibility [34].…”
Section: Introductionmentioning
confidence: 99%
“…The role of laser linewidth in conversion of laser phase noise to amplitude noise in a resonant atomic vapor was analized in [15]. Different behavior of optical spin noise spectra in Rb vapor for homogeneous and inhomogeneous broadenings was demonstrated in [16]. Applications of spin noise spectroscopy for studies of magnetic resonances, linear optics, and Raman scattering were addressed in [17][18][19].…”
Section: Introductionmentioning
confidence: 99%